Education Formulation for Gen-Z According to the Qur'an: Views of the Professor at UIN North Sumatra Towards Indonesia Emas 2045 - Hamdah Noor Halimatusyakdia; Muhammad Ali Azmi Nasution; Sholahuddin Ashani (Dinasti Publisher, 2024)
This research examines the perspectives of two Professors from UIN North Sumatra regarding the formulation of education for Generation Z based on the Qur'an, with the aim of exploring educational values that can guide this generation to reach their full potential and respond to Indonesia's Golden Vision 2045. The research method used is descriptive qualitative with an in-depth interview approach. Data were analyzed using Miles and Huberman's interactive qualitative data analysis techniques. The results of the study indicate the importance of integrating Qur'anic values such as honesty, discipline, hard work, and ethics in education to shape academically intelligent, morally upright, and integrity-driven generations. The practical implications of this research contribute to curriculum development and holistic educational strategies, as well as provide guidance for education policymakers to support Indonesia's Golden Vision 2045. It is hoped that the findings of this research will inspire positive changes in Indonesian education, leading to a bright and sustainable future.